A Standardized Education Checklist for Parents of Children Newly Diagnosed With Cancer: A Report From the Children's Oncology Group. (July 2018) - Rodgers, Cheryl; Bertini, Vanessa; Conway, Mary Ashe; Crosty, Ashley; Filice, Angela; Herring, Ruth Anne; Isbell, Julie; Lown, DrPH, E. Anne; Miller, Kristina; Perry, Margaret; Sanborn, Paula; Spreen, Nicole; et al.
Parents of children newly diagnosed with cancer must acquire new knowledge and skills in order to safely care for their child at home. Institutional variation exists in the methods and content used by nurses in providing the initial education. The goal of this project was to develop a checklist, standardized across institutions, to guide nursing education provided to parents of children newly diagnosed with cancer. A team of 21 members (19 nurses and 2 parent advocates) used current hospital educational checklists, expert consensus recommendations, and a series of iterative activities and discussions to develop one standardized checklist. The final checklist specifies primary topics that are essential to teach prior to the initial hospital discharge, secondary topics that should be discussed within the first month after the cancer diagnosis, and tertiary topics that should be discussed prior to completion of therapy. This checklist is designed to guide education and will set the stage for future studies to identify effective teaching strategies that optimize the educational process for parents of children newly diagnosed with cancer.